PERANCANGAN SISTEM PENGISI TOKEN LISTRIK BERUMPAN BALIK PADA kWh METER PRABAYAR BERBASIS ARDUINO - Nursalim, Nursalim; Galla, Wellem F.; Syam, Sudirman; Kurniati, Sri; Rondak, Valentino A.E (Jurnal Media Elektro, 2023)
Kilo Watt Hour Meter or kWh meter is a tool for calculating the amount of electrical energy used by electricity consumers, both residential and industrial customers. The electrical energy used is then converted into the electricity price that must be paid each month. Currently, most kWh meters in circulation are smart kWh, which use electricity tokens as transaction calculations. Customers must fill in 20 token numbers via the kWh meter keypad to fill in electricity tokens. Filling in this 20-digit token is not easy, this is because usually, this type of kWh is placed in a higher place to avoid the reach of children. This placement sometimes causes problems with replenishing the token, and users must start over from the beginning. This research aims to create a tool to fill in electricity token numbers that can be controlled using an Android application, making it easier for users to fill in electricity tokens remotely via smartphone. Apart from that, this system has feedback in the form of notifications that display numbers that failed to be filled in on the kWh meter. Test results show that this system can function well from 10 meters without obstructions and 9 meters without obstructions.